Creative Problem-Solving Learning Model on Students' Ability in Determining Networks of Cuboids and Cubes - Mohammad Archi Maulyda; Umar Umar (IKIP Siliwangi, 2021)
The purpose of this study was to determine whether there was an effect of using creative problem solving learning models without the support of concrete media on the ability to determine the nets of cuboids and cubes in fourth grade students of SDN 3 Bajur. In addition, to determine whether there is an effect of using creative problem solving learning models supported by concrete media on the ability to determine the nets of cuboids and cubes in fourth grade students of SDN 3 Bajur. Experimental research technique with nonequivalent control group design. The data analysis used is Spss 16 for Windows using t-test at a significant level of 5%. The results of this study are: There is an effect of creative problem solving learning models without the support of concrete media on the ability to determine the nets of cuboids and cubes in fourth grade students of SDN 3 Bajur. There is an effect of creative problem solving learning models supported by concrete media on the ability to determine the nets of cuboids and cubes in fourth grade students of SDN 3 Bajur. The ability to determine the nets of cuboids and cubes students who follow the creative problem solving learning model supported by concrete media is better than students who follow the creative problem solving learning model without the support of concrete media in the fourth grade students of SDN 3 Bajur.